2018
DOI: 10.1080/17435390.2018.1470694
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into reactivity and (geno)toxicity of well-characterized nanoparticles of cobalt metal and oxides

Abstract: An increasing use of cobalt (Co)-based nanoparticles (NPs) in different applications and exposures at occupational settings triggers the need for toxicity assessment. Improved understanding regarding the physiochemical characteristics of Co metal NPs and different oxides in combination with assessment of toxicity and mechanisms may facilitate decisions for grouping during risk assessment. The aim of this study was to gain mechanistic insights in the correlation between NP reactivity and toxicity of three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 40 publications
(52 reference statements)
2
40
1
Order By: Relevance
“…Of the NPs tested, Mn and Mn 3 O 4 NPs caused by far the largest activation of the Srxn1-GFP reporter resulting in around 20-fold maximum increase compared with control ( Figure 4). The Sn, Sb 2 O 3 and Sb NPs were also active, inducing approximately a 7-10 fold increase (Figure 4), which is comparable to previous observations for Ni and NiO NPs [11], and for Co and CoO NPs [12]. Some induction (2.5 and 2.7-fold) was also observed for the V 2 O 5 and Ag NPs, respectively (Figure 4 and Supplementary Table S1).…”
Section: Oxidative Stress-many Nps and All Qds Induce Reporters Relatsupporting
confidence: 88%
See 1 more Smart Citation
“…Of the NPs tested, Mn and Mn 3 O 4 NPs caused by far the largest activation of the Srxn1-GFP reporter resulting in around 20-fold maximum increase compared with control ( Figure 4). The Sn, Sb 2 O 3 and Sb NPs were also active, inducing approximately a 7-10 fold increase (Figure 4), which is comparable to previous observations for Ni and NiO NPs [11], and for Co and CoO NPs [12]. Some induction (2.5 and 2.7-fold) was also observed for the V 2 O 5 and Ag NPs, respectively (Figure 4 and Supplementary Table S1).…”
Section: Oxidative Stress-many Nps and All Qds Induce Reporters Relatsupporting
confidence: 88%
“…Furthermore, Cr 2 O 3 caused a weak activation of one of the oxidative stress reporters (Srxn-1) and one of the DNA damage reporters (Rtkn). The absence of activation of any of the GFP-reporters has previously been observed in response to other NPs including TiO 2 , Fe 3 O 4 and Co 3 O 4 [10,12].…”
Section: Nontoxic Nps-several Nps Cause No Toxicity or Toxtracker Actmentioning
confidence: 51%
“…With the extraction conditions of this study, which is optimized for the detection of Cr(VI), Co is not stable in solution and is expected to precipitate in the form of Co phosphate . Nevertheless, Co was clearly detected, especially for leathers from one of the tanneries.…”
Section: Discussionmentioning
confidence: 98%
“…Co ions are involved in several cellular processes, for example, in the induction of hypoxia by the increase in the inducible HIF-1α, which, in turn, could be the cause of reduced cell proliferation [31]. Some authors [32,33] reported that at a concentration of 100 μM, like used in our experiments, Co ions may induce reactive oxygen specie synthesis, which is responsible for DNA damage that, in turn, can alter the synthesis and the activity of many signaling proteins involved in the stress response, such as cell proliferation and apoptosis induction. qPCR experiments did not reveal any important involvement in mRNA expression of those genes susceptible to metal exposure and implicated in general (HSP70, MT2A) or in specific cell processes (SDHB1, MLL, CAS3, IQSEC1).…”
Section: Discussionmentioning
confidence: 99%